PKM pada Bank sampah wahana bersama dan Rosella di Siantan Tengah Kecamatan Pontianak Utara - Asriati, Nuraini; Suci, Urai; Jamiah, Yulis (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2023)
Central Siantan is an area that has great potential in waste management business so that it becomes the center of the establishment of the Wahana Bersama (Mitra I) and Rosella (Mitra II) waste banks. The purpose of this PKM program is to accompany the waste bank: (1) get capital (credit application); (2) having a legal entity, (3) having a banking bookkeeping administration system; (4) Apply science and technology to waste collectors. In general, the PKM program targets garbage banks: (1) Having additional capital in providing facilities and payment for scavengers; (2) Having a legal entity (3) Managing the administration system of banking accounting (4) Increasing the amount of diversification of waste products; (5) There is a marketing gallery of waste products. The implementation of this program is carried out in three stages: 1) the preparation phase (survey the target location, coordinate with partners, plan outreach and training materials, divide the team's tasks according to their fields. Schedule agreements with partners; 2) implementation stage , socialization of the provision of facilities / facilities, conducting counseling, assisting the administration of banking bookkeeping), training in diversification of handicraft products from waste waste); and 3) Monetering and Evaluation Phase both internal and external. The implementation of this PKM runs smoothly, although there are obstacles in time adjustments between the team and partners, but can be overcome by implementation in the afternoon or evening or carried out during holidays.